Effectiveness of urban surface characteristics as mitigation strategies for the excessive summer heat in cities. (September 2021) - Herath, Prabhasri; Thatcher, Marcus; Jin, Huidong; Bai, Xuemei
Highlights: This paper assesses the contribution of urban surface parameters (USPs) for urban heating. Cool roofs, green roofs and vegetation ratio are highly correlated with heat reduction. Effectiveness of strategies on heat reduction differs according to the time of the day. Cool roofs perform better in heat reduction at daytime while green roofs are viable during nighttime. For the maximum effectiveness of heat reduction, changes in USPs should be implemented in overall city. Abstract: Extreme urban heat, influenced by surface characteristics, negatively affects human thermal comfort. Understanding the thermal behaviour of different urban surface parameters (USPs) at large spatial scales is essential for strategic heat mitigation. This study evaluates USPs from several perspectives to assess their comparative effectiveness as heat mitigation strategies. The Air Pollution Model (TAPM) is used to simulate the urban climate of Melbourne for summer 2019 – Australia's warmest year. Fifty-two simulations are tested to represent changes in USPs as in vegetation type, built-cover ratio, building height, green roofs and cool roofs. The results of each simulation are compared with the baseline in terms of heat indices. Roofs with high albedos are found to be the best heat mitigation for reducing daytime temperatures (0.85 albedo; −1.29 °C) while green roofs show the best nighttime efficacy (100 %, −1.15 °C). Vegetation ratio, green and cool roofs show near-linear negative relationships with heat. Cooling is found to be more effective with trees when distributed in both canyon and urban parks than only planted in street canyon. These findings underscore the significance of USP characteristics in heat mitigation that can inform strategic urban planning with spatial arrangements of green infrastructure.